2006
DOI: 10.1080/00207540500445321
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge elicitation for risk mapping in concurrent engineering projects

Abstract: Concurrent Engineering aims to incorporate the overlapping of processes in order to reduce its time-to-market and thereby sustain the existence of organizations in increasingly competitive times. Although faster product design, development, and delivery are the intended outcomes of concurrent engineering, one of the undesirable by-products is an increase in risks as a consequence of uncertainties between interdependent processes. Hence, the risks need to be identified, assessed, and mitigated together with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In concurrent engineering, the information‐absorbing downstream development phase (e.g., detail design) starts before the information‐supplying upstream phase is completed (e.g., basic design), thereby potentially reducing the overall cycle time (Clark & Fujimoto, ; Terwiesch et al, ). The main drawback of concurrent engineering is the risk of creating additional engineering rework (Mihm et al, ; Mitchell & Nault, ; Savci & Kayis, ). This happens when changes are made in the upstream phase after the preliminary start of the downstream phase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In concurrent engineering, the information‐absorbing downstream development phase (e.g., detail design) starts before the information‐supplying upstream phase is completed (e.g., basic design), thereby potentially reducing the overall cycle time (Clark & Fujimoto, ; Terwiesch et al, ). The main drawback of concurrent engineering is the risk of creating additional engineering rework (Mihm et al, ; Mitchell & Nault, ; Savci & Kayis, ). This happens when changes are made in the upstream phase after the preliminary start of the downstream phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As managers become more risk averse, they prefer first‐time‐right goals and full completion of one project stage (i.e., strict gates or high quality gates) before the next begins. Sequential engineering is viewed as a strategy to mitigate disruptions in the development process that are caused by mistakes and rework in downstream stages that are associated with a concurrent approach (Liker & Morgan, ; Savci & Kayis, ). Or, in the words of the manager cited earlier: When production fails because of design issues, the quality systems are even more strictly used next time around to make sure that we don't make any mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent engineering describes the process of having upstream and downstream tasks overlapped in order to minimize time to market (Ford & Sterman, 2003; Loch & Terwiesch, 1998; Mitchell & Nault, 2007). Plenty of research states that concurrent engineering by definition leads to additional mistakes (and thus unexpected work) because the downstream phase starts to work with preliminary information from the upstream phase (Mihm et al, 2003; Mitchell & Nault, 2007; Savci & Kayis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Kayis et al ( 9 ) develop a new risk mitigation methodology for new product and process design in CE projects. Savci and Kayis ( 10 ) concentrated primarily on knowledge elicitation techniques in the intelligent risk mapping and assessment system to identify, prioritize, analyze, and assist project managers to deal with perceived sources of CE risks. Tseng et al ( 11 ) demonstrated that not every aspect of engineering design and/or manufacturing capability is linked with customers and suppliers proactively throughout the PD process.…”
Section: Introductionmentioning
confidence: 99%